2008
DOI: 10.1002/ajmg.a.32351
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cortical hyperostosis with COL1A1 gene mutation

Abstract: Infantile cortical hyperostosis (Caffey disease) is benign and self-limiting when it presents near or after birth but it is usually lethal when it presents earlier. We present the clinical, ultrasonic, radiographic, and pathologic findings in an instructive case of early onset prenatal cortical hyperostosis. The pregnancy of a 21-year-old woman was medically terminated at 30 weeks of gestation after a diagnosis of severe osteogenesis imperfecta. Prenatal ultrasounds showed short long bones. Postmortem radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…The heterozygous mutation in the COL1A1 gene (R1014C) that was found in the present case, has previously been reported in French-Canadian, Australian, Thai and Korean kindred with the classic familial form of the disease [1][2][3][4]. This mutation causes a substitution of arginine by cysteine at position 836 within the helical domain of the α1 chain of type I collagen.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The heterozygous mutation in the COL1A1 gene (R1014C) that was found in the present case, has previously been reported in French-Canadian, Australian, Thai and Korean kindred with the classic familial form of the disease [1][2][3][4]. This mutation causes a substitution of arginine by cysteine at position 836 within the helical domain of the α1 chain of type I collagen.…”
Section: Discussionmentioning
confidence: 48%
“…Both familial and sporadic occurrences have been reported. The familial autosomal dominant form has now been found to be a collagenopathy caused by a single heterozygous missense mutation in COL1A1 (c3040C>T; p R1014C) [1][2][3][4]. Though there are several case reports of Caffey disease from India, no data regarding their genetic mutation pattern have been published.…”
Section: Introductionmentioning
confidence: 92%
“…Subsequently, other groups identified the R836C mutation in Thai, Korean, Indian and Australian kindreds with the classical familial form of the disease and in sporadic cases of the infantile and prenatal forms of disease. Taken together these studies validated the pathogenetic role of this particular amino acid substitution in Caffey disease [2124]. …”
Section: Caffey Disease Overviewmentioning
confidence: 59%
“…However, mutational analysis of COL1A1 gene in two fetuses manifesting ICH characteristics disclosed a wild genotype [18]. Kamoun-Goldrat et al [21] reported an ICH fetus terminated at 30 weeks after a diagnosis of severe osteogenesis imperfecta. A postmortem test confirmed ICH.…”
Section: Discussionmentioning
confidence: 99%